2009
DOI: 10.1158/0008-5472.can-08-4043
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of MicroRNAs in Bladder Cancer: miR-129 Is Associated with Poor Outcome and Promotes Cell Death In vitro

Abstract: microRNAs (miRNA) are involved in cancer development and progression, acting as tumor suppressors or oncogenes. Here, we profiled the expression of 290 unique human miRNAs in 11 normal and 106 bladder tumor samples using spotted locked nucleic acid-based oligonucleotide microarrays. We identified several differentially expressed miRNAs between normal urothelium and cancer and between the different disease stages. miR-145 was found to be the most down-regulated in cancer compared with normal, and miR-21 was the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
279
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(301 citation statements)
references
References 46 publications
17
279
2
3
Order By: Relevance
“…This phenomenon has been noticed in several occasions. Although it has been shown that miR-200c is consistently upregulated in prostate cancer (20), the opposite has been reported for bladder cancer (27). We conclude that the role of an individual miRNA in tumor initiation or growth is organ or cell type specific so that differences in its deregulation between different tumor entities are not a contradiction, but rather reflect different roles of its target gene or genes in different tumor types.…”
Section: Discussionmentioning
confidence: 59%
“…This phenomenon has been noticed in several occasions. Although it has been shown that miR-200c is consistently upregulated in prostate cancer (20), the opposite has been reported for bladder cancer (27). We conclude that the role of an individual miRNA in tumor initiation or growth is organ or cell type specific so that differences in its deregulation between different tumor entities are not a contradiction, but rather reflect different roles of its target gene or genes in different tumor types.…”
Section: Discussionmentioning
confidence: 59%
“…The downregulation of miR-145 ( Figure 1a) in bladder cancer specimens and urothelial cell lines, as compared with normal biopsies (Figures 1b and c) (Dyrskjot et al, 2009), prompted us to investigate whether the differences in miRNA levels measured may reflect tissue heterogeneity and/or an altered ratio of different cell types to the tumor mass, rather than tumor cell-specific expression changes. We performed ISH analysis to identify which cell type(s) expressed miR-145 (Figure 2).…”
Section: Localization Of Mir-145 In Clinical Samples By Ish Analysismentioning
confidence: 99%
“…In accordance, miRNAs have been shown to influence gene regulatory processes in, for example, development, differentiation, and disease, such as cancer (Calin and Croce, 2006;Esquela-Kerscher and Slack, 2006), in which specific miRNA signatures have been associated with different clinical outcomes (Nakajima et al, 2006;Rajewsky, 2006;Yanaihara et al, 2006;Sempere et al, 2007;Tavazoie et al, 2008;Dyrskjot et al, 2009). Approximately 50% of the known miRNAs are located within regions of genomic instability that are amplified or deleted in cancer (Calin et al, 2004), which may in part explain the aberrant expression observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-129-5p, one of the mature forms of miR-129-1 and miR-129-2, has been reported to be involved in various neoplastic processes, including GC [7][8][9]. It has been demonstrated that miR-129-5p serves as an important tumor suppressor, and overexpression of miR-129-5p could significantly decrease the cell proliferation activity of multiple tumor cell lines, such as endometrial tumor cells, lung adenocarcinoma cell lines, bladder cancer cells, and GC cells [7,[10][11][12]. Another mature form of miR-129-1 and miR-129-2, miR-129-3p, has been suggested as a diagnostic and prognostic biomarker for renal cell carcinoma (RCC), and could regulate cell migration and invasion by downregulating multiple metastasis-related genes [13].…”
mentioning
confidence: 99%